THU0359 A bio-psycho-social approach for assessing associations with changes in perceived health in recently diagnosed fibromyalgia patients. (23rd January 2014) - van Eijk-Hustings, Y.; Kroese, M.; Boonen, A.; Bessems-Beks, M.; Landewé, R.
Abstract : Background: Chronic disorders such as fibromyalgia (FM) have a high impact on all aspects of health. With regard to FM, the effect of interventions is usually quite small and surrounded by uncertainty. Therefore, a better insight in associations with improvement or worsening of perceived health is essential. Objectives: The present study aimed to understand associations with Patient Global Impression of Change (PGI-C) and changes in current health state, using the International Classification of Functioning, Disability and Health (ICF) bio-psycho-social model of health as a framework. Methods: Data from a longitudinal cohort of recently diagnosed FM patients were used. Within this cohort, patients were randomised to multidisciplinary treatment (n=108), aerobic exercise (n=47) or usual care (n=48), but only a limited number (n=68) of patients started with an intervention and only 60 patients attended >70% of the scheduled sessions of the interventions. Patients completed questionnaires covering all components of the ICF framework during the study. Principal component analysis was used to reduce the number of redundant variables within the questionnaires. Univariate and multivariate regression methods were used to explore associations with the outcome variables. Results: Principal component analysis yielded five factors which appropriately fitted the ICF framework (1). The odds of patients to improve on PGI-C was 2.4 times higher (odds ratio (OR) 2.4, 95% confidence interval (CI) 1.2 to 4.8) for those being employed in comparison to those being unemployed, and the odds of patients to improve on PGI-C was 6.4 times higher (OR 6.4, CI 2.9 to 14.5) for patients attending an intervention than for patients not attending an intervention. A longer duration of FM-related symptoms (regression coefficient (B) -0.5, CI -0.9 to -0.1) and more limitations in physical areas of body functions (B -3.3, CI -6.2 to -0.5) were independently associated with a worsening in current health state. Further analyses showed that higher levels of perceived limitations in physical and mental activities were associated with starting an intervention (OR 1.8, CI 1.2 to 2.6) and with attending an intervention (OR 1.5, CI 1.1 to 2.2). Conclusions: In the context of the ICF-framework recently diagnosed patients with FM, especially those with few reported physical limitations, will experience a better health change and express better improvement of health in case they are at work and have a positive attitude towards participating in an offered health care intervention. These findings give support to an active rather than a care-avoiding attitude of health-care workers in their contacts to patients with FM. References: Van Eijk-Hustings Y, Kroese M, Bessems-Beks M, Boonen A, Landewé R. Predicting outcome. Determining clusters of patients' characteristics which can be useful in predicting outcome in fibromyalgia. Ann Rheum Dis [abstract]. 2010;69(Suppl 3):707. Disclosure of Interest: None Declared